Untangling drivers for supplier environmental and social responsibility: An investigation in Philips Lighting's Chinese supply chain. Issue 4 (16th December 2020) - Villena, Verónica H.; Wilhelm, Miriam; Xiao, Cheng‐Yong
Abstract: This study unpacks the environmental and social dimensions of supplier responsibility and links each dimension to distinct drivers. Using stakeholder theory and the relational view, we distinguish between two main drivers: stakeholder pressures (i.e., from regulatory agencies, buying firms, and nongovernmental organizations) and relational mechanisms offered by multinational companies (MNCs) (i.e., lean trainings and relational capital). We used a multi‐method research design to study how these drivers uniquely influence supplier responsibility in an emerging‐country context. An in‐depth case study with Philips Lighting and 10 of its Chinese suppliers reveals causal inferences that link stakeholder and relational drivers with each responsibility dimension (environmental vs. social). Audit and survey data from Philips Lighting's 134 Chinese suppliers, complemented with four archival databases, bolster these inferences. Overall, the results show that supplier environmental responsibility can be fostered through both stakeholder pressures and relational drivers; whereas, supplier social responsibility is much harder to address. The integrated methods offer a fuller, more comprehensive understanding of the specifics of supplier responsibility in China and also provide recommendations for MNCs that seek to improve it.